Who benefits from the agrarian transition under violent conflict? Evidence from Myanmar. (October 2022) - Forsyth, Tim; Springate-Baginski, Oliver
Abstract: Agricultural commercialization and livelihood diversification have been proposed as ways to bring economic prosperity to rural zones after long-term violent conflict. Critics, however, argue that these market-based interventions exacerbate, rather than resolve, older social divisions, and that commercialization needs to be seen as part of agrarian transition processes. This paper contributes to the analysis of livelihoods-based interventions under violent conflict by presenting research from Kachin State, Myanmar. Drawing on 276 household surveys plus interviews, the paper argues that agrarian transition has only occurred within larger landholders who have been able to increase farm size by expanding commercial agriculture onto land historically used for shifting cultivation. Smallholders, however, have been unable to expand agriculture in this way, partly because of the reallocation of agricultural land to favored investors, including Chinese banana plantations. Meanwhile, access to non-agricultural livelihoods is largely restricted to laboring in Burmese army-controlled jade mines, or to traders arriving from outside the region. These findings indicate a different outcome to research elsewhere in Myanmar that suggests agrarian transition processes can benefit landless people; and instead supports evidence elsewhere in Asia that the agrarian transition can become "truncated" if smallholders do not participate. Making the agrarian transition inclusive requires greater attention to the ethnic, and other social barriers for participation by smallholders and rural landless, rather than facilitating commercialization alone. Highlights: Agrarian transition processes replicate rather than resolve violent conflict. The agrarian transition in Kachin benefits large landholders and external traders. Farm size increases by expanding agriculture on historic shifting cultivation land. "Land grabs" prevent smallholders from expanding production. Ethnic politics influence land tenure reforms and commercialization.